The Influence of Autograph Software Aid STAD Learning Model on Mathematic Communication Ability and Mathematic Disposition of Gender - Nida UL Husnah; Mulyono Mulyono; Asmin Asmin (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine how the effect of STAD learning model assisted by autograph software on mathematical communication skills and mathematical dispositions in terms of gender. The sample used in this study is Senior High School PAB 4. With the method of data collection literature study. The method used is literature study. The results of this study indicate that the overall STAD learning model assisted by autograph software has an effect on mathematical communication skills and mathematical dispositions, this can be seen from the results of previous studies and strengthened by the theories of experts.